MobiGanha - Serviços Inovadores para Transportes Públicos Baseados em Pagamentos Móveis - Vítor Hugo Coelho Santos (2014)
In the last few years, society has witnessed the massification of mobile devices. The possibility to access a large amount of information at any time has brought new ways to interact with the world around us and new manners to accomplish our daily tasks. This has forced many companies to reinvent themselves and to evolve, and transportation companies are not an exception to the phenomenon. By designing new services, tailored to each customer, and implementing them in an Android application with built in mobile payment capabilities, this project intends to be a solution for this problem and take the evolutionary process one step further. The presented solution revolves around a voucher and promotions systems, managed by the business owners themselves via a backoffice website, which can be acquired by the application users in the mobile device using a virtual coin, awarded to the user as a result of buying transportation titles.